2015
DOI: 10.1111/joor.12359
|View full text |Cite
|
Sign up to set email alerts
|

Shortcomings of prosthodontic rehabilitation of patients living in long‐term care facilities

Abstract: Removable dentures are a non-invasive, cost-effective prosthodontic solution for the reduced dentition. Their intended purpose is the rehabilitation of harmonious oral function and aesthetics on a long-term basis. The prevalence of removable dentures among patients of advanced age is high and the quality of the dentures is often poor. The aim of this study was to find the most important shortcomings of removable dentures and address the main targets for improving the quality of prosthodontic rehabilitation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Some previous studies have levelled criticism against the practice of oral health care at public nursing homes. Severe shortcomings of tooth and denture hygiene and the state of restorative and/or prosthodontic rehabilitation in geriatric samples at a mean age of >80 years were reviewed [27][28][29]. Staff shortage, an extensive workload, and insufficient training in oral care might account for these deficiencies at public foster homes.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have levelled criticism against the practice of oral health care at public nursing homes. Severe shortcomings of tooth and denture hygiene and the state of restorative and/or prosthodontic rehabilitation in geriatric samples at a mean age of >80 years were reviewed [27][28][29]. Staff shortage, an extensive workload, and insufficient training in oral care might account for these deficiencies at public foster homes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a high percentage of the dentures were in poor condition [26]. It is a common misconception that edentulous people who use dentures do not need dental care [39]. Dentures are exposed to abrasion and the surrounding tissues are exposed to traumatic stress and microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…One study in around 680 home residents (mean age over 85 years) found a mean DMFT score of 25.6 ± 4.2 and shortcomings of oral care and prosthodontic rehabilitation [19]. Two investigations assessed the extent of denture hygiene (in relation to cognitive status) and denture retention in residents of retirement homes (mean age over 80 years) and also identified a need for improvement of oral care and denture maintenance/fitting [20,21]. The individuals admitted to DGA at the Hospital of Innsbruck are considerably younger and usually suffer disablement not associated with age-related diseases.…”
Section: Introductionmentioning
confidence: 99%